PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN FISKUS DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA KPP PRATAMA KOTA BOGOR - Samira, Leni (Fakultas Ekonomi Universitas Djuanda, 2015)
This research is performed in order to test the influence of variabel taxpayer awareness service tax authorities and tax penalties on tax compliance in Bogor Pratama Tax Office. The population in this study is the Individual Taxpayer and Agency Income Tax 21, 22 , 23, 24, 25, 26, Value Added Tax, Sales Tax and Luxury Goods Tax on Land and Building Bogor Pratama Tax Office, with a total population of 183.506 taxpayers. Sampling was carried out using probability sampling methods, sampling methods can be determined the total sample 99,87 rounded to 100. Primary data collection method used is a survey method using questionnaires media. The data analysis technique used in this study is multiple regression analysis techniques. Based on the analysis conducted, it could be concluded that the taxpayer awareness, service tax authorities, and tax penalties have the effect of partially and simultaneously on tax compliance in Bogor Pratama Tax Office.Keywords : Taxpayers Awareness, service tax authorities, tax penalties and tax compliance.